Simpler hydrostatics component of UNBabc mapping function using nonlinear curve fitting method - Batcha, S.R. (American Institute of Physics Inc., 2016)
Mapping function models should be simplified to improve the method of calculation of tropospheric delay. For UNBabc mapping function, there are 11 mathematical operations to be carried out for getting the mapping function value. To ensure faster calculation, there is a need to simplify the mapping function models. The simplification of UNBabc mapping function model is using nonlinear curve fitting method. The UNBabc mapping function model for hydrostatics component is given in a form of continued fraction. This model has been selected to be simplified, due to its ability to achieve mapping function value, down to 2 degree of elevation angle. The comparison between the original models with the simplified models can be shown by calculating the sum of error. The number of mathematical operation can be reduced after the process of simplification of the model. The reducing percentage of original model to simplified model is up to 81 percent. Â© 2016 Author(s).